Orbital rhabdomyosarcoma - I Putu Wijana; Ida Bagus Mudita; I Nyoman Golden; Agus Kusumajaya; I Ketut Mulyadi (Indonesian Pediatric Society, 2003)
we report a case of orbital rhabdomyosa-rcoma in a 2.5 year-old female child.